2018
DOI: 10.2147/dddt.s172199
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic combination therapy of lung cancer using paclitaxel- and triptolide-coloaded lipid–polymer hybrid nanoparticles

Abstract: PurposeNon-small cell lung cancer (NSCLC) accounts for the majority of lung cancer. Lipid–polymer hybrid nanoparticles (LPNs) combine the advantages of both polymeric nanoparticles and liposomes into a single delivery platform. In this study, we engineered LPNs as the co-delivery system of paclitaxel (PTX) and triptolide (TL) to achieve synergistic therapeutic effect and reduced drug resistance.Materials and methodsIn this study, PTX- and TL-coloaded LPNs (P/T-LPNs) were fabricated by nanoprecipitation method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…9 LPNs combine advantages of both liposomes and polymers into a single platform, which is an ideal system for combinatorial delivery based on the dual-component structure. 10 pH-sensitive nanoparticles have been widely used to deliver drugs in cancer therapy due to the lower pH in tumors than in normal tissues. [11][12][13] In this study, pH-responsive LPNs were applied for the carboplatin and paclitaxel delivery.…”
Section: Introductionmentioning
confidence: 99%
“…9 LPNs combine advantages of both liposomes and polymers into a single platform, which is an ideal system for combinatorial delivery based on the dual-component structure. 10 pH-sensitive nanoparticles have been widely used to deliver drugs in cancer therapy due to the lower pH in tumors than in normal tissues. [11][12][13] In this study, pH-responsive LPNs were applied for the carboplatin and paclitaxel delivery.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the difference in pharmacokinetics between the β-elemene and DOX, it is difficult to determine the optimal dose and drug ratio to exert optimal therapeutic effects at the tumor site. The combination of multiple drugs may produce better antitumor effects and the assessment of drug-drug interactions are critical (38). CI analysis is a common method for assessing the drugs interactions in combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that the ultra-small PLHNPs (25 nm) localized in a deep tissue region of the tumor with effective PTX delivery and excellent in vivo and in vitro stability in a mouse tumor model [ 53 ]. PLHNPs facilitate the delivery of numerous single chemotherapy drugs such as temozolomide, docetaxel, salinomycin, triptolide, paclitaxel, doxorubicin, and hydroxycamptothecin, among others specifically targeting different types of cancer [ 62 , 128 , 129 ]. Single drug-loaded PLHNPs have reduced in vivo and in vitro toxicity, good biocompatibility, excellent cellular internalization, and enhanced release kinetics [ 26 , 50 , 83 ].…”
Section: Applications Of Polymer-lipid Hybrid Nanoparticlesmentioning
confidence: 99%